Pengaruh Strategi Metakognitif terhadap Kemampuan Pemecahan Masalah Matematika - Ahmad Maulana (Universitas Indraprasta PGRI, 2017)
The purpose of this research is to determine the Impacts of Metacognitive Strategy on Mathematics Problems Solving. Design used true experiment design in the form of posttest only control design. This research was done by taken two class consists of 50 students with random class sampling. Data collcection used mathematics problem solving test in the form of essay test, all questions of test was validated empirically. Data analyze used t test, after the data fulfill a series tests i.e. normality test and homogeneity test. The result is t test= 7.23 in distribution table for ?=0.05, t table = 1.74, so it can be concluded that there are significant impacts of metacognitive strategy on Mathematics Problem solving.